Great expectations [videorecording (DVD)] - Kirk, Brian, 1968-; Winstone, Ray, 1957-; Anderson, Gillian, 1968-; Suchet, David; Dickens, Charles, 1812-1870 (PBS Distribution, 2012)
Nothing is quite as it seems in this lush retelling of Dickens' classic coming-of-age story with colorful characters: conspirators, rogues, rakes, and wretches.